Restorative Justice Crime Against Child Actors In The Perspective Of Justice Theft Dignified - Puspitosari, Hervina (VJJ, 2021)
Various factors the cause of children committing crimes, especially in this discussion are children who are perpetrators of the crime of theft. Various problems of children as perpetrators of criminal acts of theft that occur. The act of a child committing theft is a violation of the law and has been regulated in the Criminal Code as formulated in the provisions of Articles 362, 363 and 365 of the Criminal Code. Various negative impacts of imposing punishment on children who commit the crime of theft causing dehumanization (decreased human values), prisonization (the influence of learning crime) and stigmatization (bad labels) are also taken into consideration in encouraging the birth of a diversion policy in Indonesia. The problem that arises is how the application of diversion to child perpetrators of the crime of theft is made aware of restorative justice in the perspective of dignified justice that prioritizes the future of the child. In child protection, there are 4 basic principles, namely: non-discrimination; the best interests of the child; survival, growth and development, respect for children's opinions. Thus, in the perspective of child protection, there is no punishment for children and there is no prison for children. So that in cases of children, perpetrators of the crime of theft should prioritize diversion against children with more emphasis on dignified justice for children.